THE ROLE OF DISPOSITION OF CONNECTING TISSUE IN THE RISE OF NONTRAUMATIC SUBARACHNOIDAL HEMORRHAGE IN YOUNG AGE - E. V. Petrova; T. F. Popova; I. A. Gribacheva; G. K. Taitubayeva (Исследования и практика в медицине)
Purpose. To identify possible effects of systemic dysmorphogenesis of connective tissue on the formation and characteristics of the course of nontraumatic subarachnoid hemorrhage at a young age, with further development of an algorithm for screening physical examination of patients with an increased risk of aneurysmal hemorrhage.Patients and methods. A group of examined patients who underwent SAH under the age of 45 years were 78 people. Methods: neurological examination according to a conventional scheme using traditional methods with assessment of the main functional systems and determining the depth of their damage, determination of constitutional types, assessment of the degree of phenotypic manifestation of DCT by the sum of scores, general clinical laboratory, neuroimaging, and statistical.In order to determine the signs of connective tissue pathology in all patients with SAH, the general examination included determining the constitution, height, weight with the definition of the Ketle index. Attention was also paid to the presence of visible small vessels on the face, chest and other parts of the body, telangiectasias, angiomas, thoracic cell deformities, scoliosis, flat feet, arachnodactyly, diastase of the rectus abdominis muscles, hernia of the anterior abdominal wall. Among the many undifferentiated phenotypic signs of DCT, external (changes in the skin and its derivatives, changes in bones, joints, spine, features of the structure of the hands and feet, peculiarities of the structure of the auricle, eyes, oral cavity, craniocephalic features) and internal (the presence of additional chords, heart valve prolapses, nephroptosis and kidney development abnormalities).Results. When examining 78 patients with subarachnoid hemorrhage at a young age, the risk factors for its development were revealed (non-closed Willisian circle (86.6%), pathological tortuosity of the cerebral vessels (81.6%), dysplastic changes in the heart (68.3%) and kidneys (63.3%), which significantly differed from the comparison group (arterial hypertension – 97.8%, heart disease (IHD, atrial fibrillation) – 53.2%, hypercholesterolemia – 97.8%.) The value of systemic dysplastic change in connective tissue in the formation and flow of SAC at young age is shown. The constitutional-anatomical and functional features, characteristic for external and internal phenotypic signs of connective tissue dysplasia in different age groups, are revealed, and the role of additional vascular risk factors in the course of SAH are found. Conclusion. The complex study of connective tissue dysplasia as a risk factor for the development of aneurysms with a clinical manifestation in the form of SAH at a young age can be used in clinical practice for the timely detection and surgical treatment of aneurysms without signs of SAH. The obtained data can become a basis for developing an algorithm for screening physical examination of patients with an increased risk of aneurysmal hemorrhage.